L’ attitude de la classe politique et de la société civile turques face au Conseil européen de Copenhague - Gültekin, Burcu (Études helléniques / Hellenic Studies, 2003)
Turkey's political class and civil sociecy had been mobilized, in their entirety, in favour of the candidacy of their country to the E.U. before the Copenhagen Summit. A sentiment of deception dominated, at first, amongst the Turks at the close of that Summit, which had adjourned the decision of the Europeans on the date for opening of accession negotiations. Later, however, the idea had been accepted that the results of Copenhagen were the best possible. The signing of the Treaty for the accession of the Republic of Cyprus in the E.U. on April 16 in Athens, had been felt in Ankara as a great diplomatic defeat, but the Turks understood that it is urgent, for their own interest, to settle the Cypriot question.